Membrane cleaning using electric pulse in dead end ultrafiltration of proteinaceous solution - A.L. Ahmad';; I.A. Azid (Universitas Gadjah Mada, 2001)
Dead end ultrafiltration of Bovine Serum Albumine (BSA) using a polymeric membrane has been studied. Membrane fouling for such fine biological product due to the formation of filter cake and adsorption of the proteinaceous solution is the major bottleneck for such separation process. The application of electric pulses has shown an effective means in cleaning the membrane and reducing the fouling rate for dead-end ultrafiltration of BSA. The flux is significantly increased by both electrophoretic motion of solutes away from the membrane surface and electro-osmosis occurring in the filter cake. An automated experimental rig equipped with data acquisition system has been developed to test the effectiveness and performance of such membrane cleaning. The improvement of flux becomes more pronounced with increasing electric field strength. The effects of other processing variables such as pulse interval, pulse duration, ionic strength of the electrolyte, pH of the solution and solution concentration were studied on this membrane cleaning technique. Data are analysed for its average flux, average cake concentration, average percentage of cake and water recovery for every cleaning condition. It is found out that the chemical and physical properties of the solution (pH and ionic strength of the electrolyte) have a great effect on this membrane cleaning method. Protein solution at pH 8 and 0.0 lM ionic strength of the electrolyte gave the best membrane cleaning performance. Shorter pulse interval and with relatively 10 seconds pulse duration are the optimum conditions on application of pulse to remove the filter cake from the membrane.